Achieving Superior Marketing Performance Through Digital Transformation and Consumer Trust-Based E-Commerce Adoption - Galih Setya Nugraheni; Naufa Dw Ayu Anggraeni; Gita Sugiyarti (Proceeding of The International Conference on Business and Economics, 2026)
Micro, Small, and Medium Enterprises (MSMEs) face increasing pressure to adapt to digital transformation and e-commerce in order to enhance marketing performance; however, their implementation is often constrained by limited technological utilization and low levels of consumer trust. This study aims to analyze the role of consumer trust as a mediating variable in the relationship between digital transformation, e-commerce adoption, and the marketing performance of MSMEs. A quantitative approach was employed using a survey of MSME actors in Semarang City to collect data on technology usage, consumer trust levels, and marketing performance outcomes. The results indicate that digital transformation and e-commerce adoption have a positive effect on marketing performance, while consumer trust significantly strengthens this relationship as an intervening variable. The study concludes that the success of MSME digitalization is highly dependent on the ability to build consumer trust; therefore, digital marketing strategies should prioritize enhancing credibility and improving customer experience.